Occlusal trauma inhibits osteoblast differentiation and bone formation through IKK‐NF‐κB signaling. Issue 5 (2nd October 2019) - Xu, Weizhe; Lu, Ying; Yue, Junli; Lu, Wanlu; Zhou, Wei; Zhou, Xuedong; Ye, Ling; Zheng, Qinghua; Zhang, Lan; Huang, Dingming
Abstract: Background: Occlusal trauma is an important factor promoting bone loss caused by periodontal diseases. Although there are reports of traumatic force promoting bone resorption in periodontal diseases, no studies examining the inhibition of bone formation by traumatic force and the underlying mechanism have been reported. The aim of this study was to investigate the mechanism whereby traumatic force inhibits bone formation. Methods: MC3T3‐E1 cells were induced to undergo osteogenic differentiation and subjected to cyclic uniaxial compressive stress with or without stimulation with Pg . LPS. The expression of osteoblast markers and the activation of IKK‐NF‐κB signaling were evaluated in vitro. Then, MC3T3‐E1 cells were induced to undergo osteogenic differentiation and subjected to cyclic uniaxial compressive stress with or without IKK‐2 Inhibitor VI. The expression of osteoblast markers was determined. Then, the classic Wnt signaling pathway (β‐catenin, Gsk3β, p‐Gsk3β, and Dkk1) was further evaluated in vitro. Finally, occlusal trauma was induced in Wistar rats with or without the injection of IKK‐2 Inhibitor VI, to evaluate changes in bone mass and IKK‐NF‐κB and Wnt/β‐catenin signaling in vivo. Results: After stimulation with Pg . LPS and traumatic force, IKK‐NF‐κB signaling was significantly activated in vitro. The expression of osteoblast markers and the activity of alkaline phosphatase in MC3T3‐E1 cells declined after traumatic force loading and were rescued when IKK‐NF‐κB signaling was blocked. Wnt/β‐catenin signaling was accordingly inhibited upon force loading, but this inhibition was reversed when IKK‐NF‐κB was antagonized in vitro. X‐ray and Micro‐CT analysis of the mandibles of the rats as well as HE and TRAP staining showed that bone loss induced by occlusal trauma declined after IKK‐NF‐κB was inhibited. The expression of p65 and IκBα was increased when occlusal trauma was induced in Wistar rats, whereas β‐catenin, OCN, and Runx2 levels were decreased. After blocking IKK‐NF‐κB, significant upregulation of β‐catenin, OCN, and Runx2 was observed in rats suffering from occlusal trauma. Conclusions: IKK‐NF‐κB signaling could be activated by traumatic force or occlusal trauma. Its activation promoted the degradation of β‐catenin, ultimately inhibiting osteogenic differentiation in vitro and bone formation in vivo.